2021
DOI: 10.3390/en14216937
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of the Static Excitation Systems of Synchronous Generators with the Use of Hardware-In-the-Loop Technologies

Abstract: In this paper, testing and diagnosis methods for the static excitation systems of power plant synchronous generators using Hardware-In-the-Loop technology are described. These methods allow a physical excitation system to be connected to a real-time model of a power plant unit. A feature of a static excitation system is the presence of generator self-excitation—that is, when the input voltages of the excitation system are defined by a synchronous generator. These voltages are determining by the digital model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Examples of such models for electrical drives with a three-phase IM are presented in [34,35], and power systems with wind turbines are discussed in [36]. Reference [37] presents mathematical models of electrotechnical systems with synchronous machines and technology for use in testing synchronous generator excitation systems. The AVIS method is used for creating models of power systems with nonlinear elements [38].…”
Section: Mathematical Model Description Of Symmetrical 6pim Taking In...mentioning
confidence: 99%
“…Examples of such models for electrical drives with a three-phase IM are presented in [34,35], and power systems with wind turbines are discussed in [36]. Reference [37] presents mathematical models of electrotechnical systems with synchronous machines and technology for use in testing synchronous generator excitation systems. The AVIS method is used for creating models of power systems with nonlinear elements [38].…”
Section: Mathematical Model Description Of Symmetrical 6pim Taking In...mentioning
confidence: 99%
“…A feature of the proposed mathematical model of the switch control-based multi-winding IM is using the method of the average voltages in the integration step (AVIS) [25][26][27]. This method has repeatedly been used by authors, and its high efficiency was demonstrated during a simulation of power schemes with synchronous machines and induction machines, as well as power systems with nonlinearities [26,[28][29][30]. The advantages of the method are high calculation speed and numerical stability, which make it suitable for creating real-time models.…”
Section: Mathematical Model Of Multi-winding Immentioning
confidence: 99%
“…The advantages of the method are high calculation speed and numerical stability, which make it suitable for creating real-time models. These real-time models are able to work for a long time in interaction with physical objects (hardware-in-the-loop technology) [29,31,32].…”
Section: Mathematical Model Of Multi-winding Immentioning
confidence: 99%
“…This approach has proven itself in the synthesis of real-time models of various electromechanical systems [24][25][26] and has been used to set up excitation systems for synchronous generators [27,28], including at the South Ukrainian NPP. The application of this approach in the EAF model will require the creation of a slightly different from the existing model of the arc space.…”
Section: Introductionmentioning
confidence: 99%